Given that
x
,
y
and
z
are positive real that are not 1, evaluate
x l o g ( z y ) × y l o g ( x z ) × z l o g ( y x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
use 1 0 b = x where b = l o g x
Similar method here. You will get 1 0 n where n = ( l g x ) ( l g y − l g z ) + ( l g y ) ( l g z − l g x ) + ( l g z ) ( l g x − l g y ) = 0 . It follows that 1 0 0 = 1 .
Problem Loading...
Note Loading...
Set Loading...
Let the expression be equal to a. take log on both sides. the exponents become coefficients. use log(n/m)=logn -logm and expand the whole of the expression. we see terms cancel out and finally we get log a =0 which means that a equals one